Understanding Student Engagement and Writing Skills through Interactive Game Based Activities among Young Learners in EFL Classrooms - Dama Yanti, Ade; Bahri, Seful (International Journal of Language Teaching and Education, 2026)
This study explores the relationship between student engagement and writing skills through interactive game-based activities in an elementary EFL classroom. Elementary students often display varying levels of participation and experience difficulties expressing their ideas in English, both orally and in writing. While previous studies have primarily emphasized learning outcomes, this research focuses on students’ engagement during interactive activities and their responses to writing tasks in a game-based learning environment. A qualitative case study design was employed involving 11 sixth-grade students from a public elementary school in Simalungun Regency. Data were collected through classroom observations, semi-structured interviews, and documentation, then analyzed interpretively to examine students’ behavioral, emotional, and cognitive engagement in writing activities and their learning experiences. The findings are expected to demonstrate how interactive games enhance classroom engagement and support students’ writing development. Game-based activities are anticipated to create a more enjoyable and relaxed learning environment, encouraging active participation with peers, teachers, and learning materials. The study is also expected to show that interactive games help students with limited verbal abilities express their ideas more effectively in written English. Overall, this research provides insights into the role of game-based learning in fostering student engagement and improving writing skills in EFL classrooms. It also offers practical guidance for teachers seeking to implement interactive, meaningful, and student-centered English instruction for young learners.